Legal Regime of Telework in Peru: Individual aspects of the issue - Arce Ortiz, Elmer (2024)
In September 2022, Law 31572 repealed Law 30036, thereby modifying the legal regime of teleworking in Peru. In this context, this work aims to study and describe, in normative terms, the new legal regime that Law 31572 imposes on teleworking. The new Law refers to a special modality of provision of work, requiring a precise study centered on the impact of teleworking on essential elements such as the employment contract, its benefits, termination, among others. This means that Law 31572 regulates specific situations related to all teleworkers, regardless of the general labor legislation, namely Labor Productivity and Competitiveness Law. This study will address these specific rules.